Quantitative Assessment of Selected Financial Aspects of Small and Medium-sized Enterprises in a Developing Country - Mura, Ladislav
Kvantitatívna analýza niektorých finančných aspektov malých a stredných potravinárskych podnikov na Sri Lanke.